Uptake of α-Ketoglutarate by Citrate Transporter CitP Drives Transamination in Lactococcus lactis - Pudlik, Agata M. (American Society for Microbiology, 2013)
Transamination is the first step in the conversion of amino acids into aroma compounds by lactic acid bacteria (LAB) used in food fermentations. The process is limited by the availability of α-ketoglutarate, which is the best α-keto donor for transaminases in LAB. Here, uptake of α-ketoglutarate by the citrate transporter CitP is reported. Cells of Lactococcus lactis IL1403 expressing CitP showed significant levels of transamination activity in the presence of α-ketoglutarate and one of the amino acids Ile, Leu, Val, Phe, or Met, while the same cells lacking CitP showed transamination activity only after permeabilization of the cell membrane. Moreover, the transamination activity of the cells followed the levels of CitP in a controlled expression system. The involvement of CitP in the uptake of the α-keto donor was further demonstrated by the increased consumption rate in the presence of l-lactate, which drives CitP in the fast exchange mode of transport. Transamination is the only active pathway for the conversion of α-ketoglutarate in IL1403; a stoichiometric conversion to glutamate and the corresponding α-keto acid from the amino acids was observed. The transamination activity by both the cells and the cytoplasmic fraction showed a remarkably flat pH profile over the range from pH 5 to pH 8, especially with the branched-chain amino acids. Further metabolism of the produced α-keto acids into α-hydroxy acids and other flavor compounds required the coupling of transamination to glycolysis. The results suggest a much broader role of the citrate transporter CitP in LAB than citrate uptake in the citrate fermentation pathway alone.